1990
DOI: 10.1177/38.10.2144864
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical localization of calcium and Ca2+,Mg2(+)-adenosine triphosphatase in colchicine-altered rat incisor ameloblasts.

Abstract: Colchicine is known to affect secretory, transport, and degradative functions of ameloblasts. The effects of colchicine on membrane-associated calcium and Ca2+,Mg2(+)-ATPase in secretory and maturation ameloblasts were investigated cytochemically. The pyroantimonate (PPA) method was used for localizing calcium and a modified Wachstein-Meisel medium was used to localize Ca2+,Mg2(+)-ATPase. Sections representing secretory and early maturation stages were examined by transmission electron microscopy. Morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Radioautographic studies with 45 Ca 2+ [23] and ultrastructural detection of Ca 2+ antimonate precipitates in plasma membranes [8] presented evidence that RE ameloblasts but not SE ameloblasts actively transport Ca 2+ into the enamel space. In the ameloblast layer of non-fluorotic wild-type mice, narrow gaps of immunonegative staining for NCKX4 were noted similar as for AE2 [24], resembling groups of SE ameloblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radioautographic studies with 45 Ca 2+ [23] and ultrastructural detection of Ca 2+ antimonate precipitates in plasma membranes [8] presented evidence that RE ameloblasts but not SE ameloblasts actively transport Ca 2+ into the enamel space. In the ameloblast layer of non-fluorotic wild-type mice, narrow gaps of immunonegative staining for NCKX4 were noted similar as for AE2 [24], resembling groups of SE ameloblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced secretion of buffer by ameloblasts could explain why the acidic RE bands in fluorotic enamel are wider [3, 4]. Ultrastructural detection of pyroantimonate precipitable Ca 2+ in plasma membranes of ameloblasts suggested that secretory and RE ameloblasts but not SE ameloblasts transport Ca 2+ across their membranes [8]. Exposure to F reduces the number of pyroantimonate precipitable Ca 2+ in the intercellular space of secretory ameloblasts [9] suggesting that fluoride reduced Ca 2+ transport is one factor responsible for hypomineralization of fluorotic enamel.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that Ca2+,Mg2+-ATPases are enriched along the apical plasma membranes of ruffle-ended, but not smooth-ended, ameloblasts (Crenshaw and Takano, 1982;Takano et al, 1986;Sasaki et al, 1987a;Sasaki and Garant, 1987;Salama et al, 1989a;Eisenmann et al, 1990Eisenmann et al, , 1992Borke et al, 1993;Takano, 1995;Zaki et al, 1996). These ATPases seem very sensitive to anti-microtubular agents, which upset both the apical distribution pattern of the enzymes and the normal 45Ca uptake patterns seen in enamel (Eisenmann et at., 1990(Eisenmann et at., , 1992.…”
Section: Ion Transportmentioning
confidence: 95%
“…These ATPases seem very sensitive to anti-microtubular agents, which upset both the apical distribution pattern of the enzymes and the normal 45Ca uptake patterns seen in enamel (Eisenmann et at., 1990(Eisenmann et at., , 1992. Most workers, therefore, favor the idea that, regardless of how calcium ions get to the apical membrane of the cell, the ruffle-ended ameloblasts actively pump the calcium ions out of the cell into enamel using membrane ATPases (Bawden, 1989;Zaki et al, 1996).…”
Section: Ion Transportmentioning
confidence: 97%
See 1 more Smart Citation